Accuracy and acceptability of survivorship care plans: results of a pilot study. Issue 3 (5th March 2020) - Koczwara, Bogda; Doherty, Tracey N.; Hislop, Chantelle C.; Cameron, Kate; Bessen, Taryn; Christensen, Chris; Corsini, Nadia; Fitzgerald, Michael K.; Loft, Nicole; Poprawski, Dagmara M.; Turpin, Kate H.; Eckert, Marion C.
Abstract: Survivorship treatment summaries and care plans are increasingly incorporated into cancer care but there are limited data on their accuracy and acceptability. We have evaluated written care plans developed as part of a once‐off, nurse‐led survivorship consultations across four medical oncology clinics in South Australia as part of a state‐wide pilot. While the accuracy of treatment summaries was high, level of detail in care plans was moderate to low, as was survivors' perception of plans' utility.